Hyperfine and tunneling effects in the microwave spectrum of N-2-OCS - Connelly, P; Duxon, S; Kennedy, S; Howard, B; Muenter, J (1996)
A- and b-type rotational transitions of N2-OCS between 6 and 18 GHz have been recorded using a pulsed, supersonic nozzle, Fourier-transform microwave spectrometer. The rotational spectrum is indicative of a planar, T-shaped complex, with the nitrogen molecular axis oriented toward the carbon of OCS. Symmetry effects in the nuclear quadrupole hyperfine structure imply that the nitrogen nuclei are effectively equivalent due to rotation of the nitrogen molecule. The resulting symmetric and antisymmetric combined nuclear spin and tunneling states are associated with slightly different rotational and hyperfine parameters. First-order quadrupole and spin-rotation interactions are used to fit the hyperfine structure, and the hyperfine dependence on rotational state is investigated. An instance of accidental near-degeneracy has allowed determination of the χab off-diagonal quadrupole coupling constant for the symmetric state. Deduced structural parameters have been compared with a model based on distributed multipole, dispersion, and hard sphere interactions. The quadrupole coupling constants of the two tunneling symmetry states have been used to model the angular tunneling potential, giving a barrier to rotation of 40.44 cm-1 and a tunneling frequency of 2450.0 GHz. © 1996 Academic Press, Inc.